MaCDI : isu-isu dalam pentadbiran dan pembangunan tanah - Mohamad, Mohaizi (2004)
Effective land administration projects in developing countries help to improve the social and economic lives of millions of poor people. Land administration projects breakdown a key development constraint, i.e. allowing land to be owned, protected, and traded. This unlocks an inherent value in land that can be harnessed for improving social and economic growth. Few development projects can claim such a high and wide reaching potential development impact. The benefits of land administration projects are in areas of social, gender, financial, economic, and environment. This study focused on undertaking land administration projects in the future, and how their selection, design and implementation could be improved by following the concept of Malaysian Geospatial Data Infrastructure (MaCGDI), which allows all the Land Related Agencies to take part in land administration projects in the cost-effective way. These also includes analyses of developing "cost-effective" way among few GIs Web Based projects that has been developed before.